Life Cycle Assessment of Green Methanol Production Based on Multi-Seasonal Modeling of Hybrid Renewable Energy and Storage Systems - Guleroglu, Huseyin; Yumurtaci, Zehra (MDPI, 2025)
This study evaluates the environmental implications of green methanol production under seasonal energy variability through a dual-comparative analytical framework. The research employs ReCiPe 2016 Endpoint (H) methodology to assess four seasonal renewable energy configurations (with varying solar-wind ratios across seasons) against conventional grid-based production, utilizing a hybrid battery storage system combining lithium-ion and vanadium redox flow technologies. The findings reveal significant environmental benefits, with seasonal renewable configurations achieving 24.38% to 28.26% reductions in global warming potential compared to conventional methods. Monte Carlo simulation (n = 20,000) confirms these improvements across all impact categories. Our process analysis identifies hydrogen production as the primary environmental impact contributor (74-94%), followed by carbon capture (5-13%) and methanol synthesis (0.5-4.5%). Water consumption impacts show seasonal variation, ranging from 16.55% in summer to 11.62% in winter. There is a strong positive correlation between hydrogen production efficiency and solar energy availability, suggesting that higher solar energy input contributes to improved production outcomes. This research provides a framework for optimizing sustainable methanol production through seasonal renewable energy integration, offering practical insights for industrial implementation while maintaining production stability through effective energy storage solutions.
Keywords: LCA of green methanol; renewable energy; seasonal energy variability; solar-wind hybrid systems; hybrid energy storage systems; alkaline water electrolysis; water consumption; carbon capture and purification; vanadium redox flow batteries; lithium-ion batteries; environmental implication; dual-comparative analytical framework; HYDROGEN-PRODUCTION; Science & Technology - Other Topics; Environmental Sciences & Ecology